Supported employment interventions for workplace mental health of persons with mental disabilities in low-to-middle income countries: A scoping review. - Edwin Mavindidze; Clement Nhunzvi; Lana Van Niekerk (PLoS ONE)
Objective To review the evidence of supported employment interventions in low-to-middle income countries, documents their impact for persons with mental disorders in the open labour market and well as support decision making for its wider implementation in the workplace. Design The scoping review is conducted following guidelines in the Arksey and O'Malley (2005) Framework. Data sources and eligibility Eleven databases which are PubMed, Scopus, Academic Search Premier, the Cumulative Index to Nursing and Allied Health Literature, Africa-Wide Information, Humanities International Complete, Web of Science, PsychInfo, SocINDEX, Open Grey and Sabinet were searched for articles published between January 2006 and January 2022. Both peer-reviewed articles and grey literature were eligible if they were on supported employment interventions in low-to-middle income countries. Only articles published in English were included. Study appraisal and synthesis Articles were screened at title, abstract and full article levels by two independent teams with the use of Rayyan software. Deductive thematic analysis was used to synthesize evidence on the supported employment interventions implemented in LMICs, capturing evidence of their outcomes for persons with mental disabilities securing competitive work. Results The search yielded 7347 records and after screening by title and abstract, 188 studies were eligible for full article screening. Eight studies were included in this scoping review. Thematic descriptions of the findings were based on the availability of supported employment interventions within the context, the type of supported employment interventions as well as mental health and vocational outcomes in the workplace. Conclusions There is limited evidence of supported employment interventions in low-to-middle income countries despite the promising potential it has as an intervention to address mental health problems in the workplace and facilitate work participation by persons with mental disabilities.